On the Representation of Demand-Side Management in Power System Models - Alexander Zerrahn; Wolf-Peter Schill (Energy, 2015)
DSM (demand-side management) merits increased attention by power system modelers. Numerical models should incorporate DSM constraints in a complete and consistent way. Otherwise, flawed DSM patterns and distorted conclusions on the system benefits of demand-side management are inevitable. Building on a model formulation put forward by Göransson et al. (2014), it is first suggested to include an additional constraint that resolves the problem of undue DSM recovery. Afterwards, an alternative model is introduced that does not impose a specific temporal structure on load shifts and thus increases the real-world applicability of DSM modeling. The formulation presented here, which is both concise and linear, could readily be included in a wide range of numerical models.
Additional information: This is the accepted manuscript of an article published in Energy vol. 84 (2015), p. 840-845, available online at: http://dx.doi.org/10.1016/j.energy.2015.03.037
Keywords: 330; Demand-side management; Demand response; Load shifting; Energy modeling; Energieökonomik; Energieversorgung; Elektrizitätswirtschaft; Nachfrage